Analysis of The Influences of Regulatory Support and Customer Relationship Management on Green Transportation Throught Cost efficiency at PT Pos Indonesia - Rahman Fathan; Maniah Maniah; Erna Mulyati (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study aims to analyze the influence of regulatory support and customer relationship management on green transportation implementation through cost efficiency as a mediating variable at PT Pos Indonesia (Persero). The research is motivated by the increase in logistics activities due to the growth of e-commerce, which drives distribution needs while simultaneously intensifying the challenge of reducing carbon emissions in the transportation sector. The study employs a quantitative approach with descriptive and verificative methods. Data were obtained through questionnaires distributed to 200 employees of PT Pos Indonesia (Persero) in various regions of Indonesia using a purposive sampling technique. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that regulatory support has a positive and significant effect on cost efficiency (β = 0.544; t = 12.727) and green transportation implementation (β = 0.482; t = 9.527). Customer relationship management also has a positive and significant effect on cost efficiency (β = 0.449; t = 8.948) as well as on green transportation implementation (β = 0.333; t = 6.780). In addition, cost efficiency has a positive effect on green transportation implementation (β = 0.288; t = 5.935) and partially mediates the influence of both independent variables on green transportation implementation. This study is expected to serve as a reference for the development of green logistics and the implementation of green transportation at PT Pos Indonesia (Persero).